Developing E-Module Accounting Cycle based on Problem-Based Learning (PBL): Can it Improve Students' Critical Thinking Abilities? - Yeyen Suryani; Iskandar; Fifit Nabhan Nurfitriani; Rani Tania Pratiwi; Muhammad Hasan; Nur Arisah; Nur Aeni; Akhtem A. Dzhelilov (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
The limitations of teaching materials in the new curriculum, namely the independent curriculum and technological advances. It has a good impact on education to support the achievement of 21st century skills. E-modules could be used as an alternative learning resource that was practical and contextual, because they could be used anywhere and the material presented was relevant to real life. The article aimed to produce e-module based on PBL valid, practical, and accounting cycles to determine the effectiveness of the e-module on students' critical thinking skills. The researchers used development research, adapting the ADDIE model (analyze, design, develop, implement, and evaluate). In testing the effectiveness of this e-module, there was a significant increase because the value of the learning effectiveness of students after being given treatment was higher than without being given treatment. The implication of this research showed that educators must implement PBL assisted by e-modules, especially in accounting subjects, to improve students' critical thinking. Students were able to formulate learning problems, analyze problems, students used clear language, and draw learning conclusions. It gave an implication provision for students to develop their critical thinking skills. An important implication for the future that could be made was by paying attention to designs that were more appropriate to student needs, integrating content that was relevant to real life, and providing adequate training to teachers, it can increase the effectiveness of the module in improving students' critical thinking abilities.